2019
DOI: 10.3390/ani9040136
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Use of Insect Meal from Spodoptera littoralis and Bactrocera zonata for Feeding Japanese Quail Chicks

Abstract: A transformation of current livestock production towards a more sustainable operation is crucial to face nutritional and environmental challenges. There is an urgent demand for more sustainable high-quality feed sources to reduce environmental costs. Insects pose a potential alternative since they can be reared sustainably on food and feed residues. Know-how in mass rearing already exists for insect species used in biological pest control, such as the African cotton leafworm Spodoptera littoralis and the peach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
6
14
1
2
Order By: Relevance
“…Crude fibre levels were generally <10%, and lowest in R. differens. The crude fibre contents of R. differens, H. illucens, and S. littoralis corresponded well with those reported by other authors i.e., R differens: 1.8-2.7% [24]; H. illucens: 7% [4]; S. littoralis: 10.7% [25], whereas the levels determined in A. domesticus were about half the levels (14.9-22.1%) reported elsewhere [23]. Crude fibre also includes chitin and complex carbohydrates such as cellulose and lignin that might be present in the insects' gut [26], and therefore variability may arise depending on preparation processes such as the degutting, cleaning and removal of parts, or the inclusion of a starvation regime prior to harvesting [15].…”
Section: Proximate Composition Of Raw Insectssupporting
confidence: 90%
See 2 more Smart Citations
“…Crude fibre levels were generally <10%, and lowest in R. differens. The crude fibre contents of R. differens, H. illucens, and S. littoralis corresponded well with those reported by other authors i.e., R differens: 1.8-2.7% [24]; H. illucens: 7% [4]; S. littoralis: 10.7% [25], whereas the levels determined in A. domesticus were about half the levels (14.9-22.1%) reported elsewhere [23]. Crude fibre also includes chitin and complex carbohydrates such as cellulose and lignin that might be present in the insects' gut [26], and therefore variability may arise depending on preparation processes such as the degutting, cleaning and removal of parts, or the inclusion of a starvation regime prior to harvesting [15].…”
Section: Proximate Composition Of Raw Insectssupporting
confidence: 90%
“…Furthermore, the fat contents of H. illucens and A. domesticus were within the range reported by other researchers: 9.8-22.8% for A. domesticus [23] and 15-35% for H. illucens [4]. The fat contents of R. differens and S. littoralis were approximately half the levels reported elsewhere i.e., 42.2-54.3% for R. differens [24] and 33% for S. littoralis [25]. Means in the same column followed by the same capital letters, and means in the same row followed by the same small letters are not significantly different (p < 0.05; n = 3).…”
Section: Proximate Composition Of Raw Insectssupporting
confidence: 82%
See 1 more Smart Citation
“…The protein and carbohydrate contents are especially important for the immune response and survival of insects (Cotter et al, 2011;Ponton et al, 2020). Larvae of the Egyptian cotton ball armyworm Spodoptera littoralis (potential feed for quail chicks, (Sayed et al, 2019) challenged with a baculovirus, showed higher immune response and survival when fed on a diet with a high protein content relative to carbohydrate content (P:C ratio) (Lee et al, 2006). In the same study, a group of larvae were allowed to select among diets with varying P:C ratio after being challenged with the virus; those larvae who survived the infection showed a preference for the diet with higher P:C ratio, in comparison to control and dying larvae, suggesting a purposeful change in their feeding…”
Section: Dietary Changes and Nutrient Deficienciesmentioning
confidence: 99%
“…This is particularly important for the European countries, with well-developed aquaculture industry, i.e., Norway, Spain, UK, France, Italy and Greece, since the reliance on fishmeal-based aquafeeds has greatly contributed to the increase in production cost. Apart from aquafeeds, the suitability of insect meals as ingredient of poultry diets has been documented by several studies [ 33 , 34 , 35 , 36 ], whereas it is believed that soon the EU will authorize the use of insects for the poultry and swine industry.…”
Section: Introductionmentioning
confidence: 99%